Actors, puppets, Girls: Little Women and the collective Bildungsroman. Issue 12 (1st December 2020) - Trumpener, Katie
ABSTRACT: This essay spans a long and somewhat unconventional arc – from Goethe's 1795–6 Wilhelm Meister's Apprenticeship Years to Lena Dunham's recent television series Girls. On the one hand, it focuses on the question of collectivity and coercion in Goethe's Ur-Bildungsroman, set initially among itinerant actors, joined and then partly led by a bourgeois scion escaping from his upbringing. Yet the novel differs in important ways from the picaresque. The essay argues, moreover, that Dunham's Girls, in the plural, with its collective protagonists, is only the latest iteration in a long tradition of female Bildungsromane (from Austen's 1813 Pride and Prejudice to Louisa May Alcott's 1868–9 Little Women, the widely-popular 1890s Australian girls' novels of Ethel Turner and Louisa Mack, and subsequent family books by E. Nesbit, Noel Streatfeild, etc.) featuring a small sibling or friend group in lieu of a single protagonist. These grouped characters, traversing trials and incidents together, or in contrast to one another, enabled a more faceted account of female social models, developmental variables, and struggles for agency. To chronicle one's own life, on film, as fiction, and as part of a generational plural, is to reground the Bildungsroman itself as a thoroughly self-interrogatory and feminist practice.